2020
DOI: 10.3390/su122410291
|View full text |Cite
|
Sign up to set email alerts
|

Walking toward Metro Stations: the Contribution of Distance, Attitudes, and Perceived Built Environment

Abstract: Walking as an active means of travel is important as a sustainable mode of transport. Moreover, the level of walking in the surrounding areas of metro stations would contribute to maintaining the minimum rate of physical activity and, therefore, inhabitants’ general health. This study examined the impacts of walking attitude, walking distance, and perceived built environment on walking behavior for reaching the metro stations in Shiraz, Iran. Three metro stations were selected and a quantitative approach was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
(139 reference statements)
1
15
0
1
Order By: Relevance
“…This study also showed that distance was the main barrier preventing utilitarian walking to routine destinations, confirming previous research in this field [15,27]. Distance is the key determinant of walking particularly for the elderly population due to the physical effort required [90].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study also showed that distance was the main barrier preventing utilitarian walking to routine destinations, confirming previous research in this field [15,27]. Distance is the key determinant of walking particularly for the elderly population due to the physical effort required [90].…”
Section: Discussionsupporting
confidence: 88%
“…Walking to shops is also a very common travel purpose, and the presence of facilities such as grocery stores, supermarkets, restaurants, banks, and fitness centers, among others, has a great impact on inducing utilitarian walking [21][22][23][24][25]. Walking to public transport is a common determinant too, as the use of public transport generally involves walking to bus stops and train stations [26,27]. For that reason, public transport has been considered as active travel, because the distance travelled from the stop to the destination can make a significant contribution to daily physical activity and healthy lifestyles [28].…”
Section: Categories Of Walkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main spatial criteria considered as input are as follows: distance from main streets, distance from highways, distance from the non-residential land use, number of patients in the hospitals and population density, and location of patients’ financial transaction within [0-500] and [500-1000] meters. The selected service area distances are based on experts’ opinions where the pedestrians travel on foot on an average of 500 m and the drivers travel within 1000 m to get a specific location on purpose ( Neysani Samany et al, 2013 , Paydar et al, 2020 , Omidipoor et al, 2021 ). The target is regarded as the location of patients in these regions.…”
Section: Methodsmentioning
confidence: 99%
“…Audit (SPACES, PEDS, or other types) and GIS have been used for the process of objective measurements of the built environments [31,111,112]. The perceived built environment has been measured through standard survey questionnaires such as "Neighborhood Environment Walkability Scale" (NEWS) [31,93,113]. According to Smith [114], perceived measures of microscale built-environment features such as the aesthetic-related features contribute to predicting walking behavior more effectively.…”
Section: The Contribution Of Built Environment Factors To Walking/cycling Behavior and The Impacts Of The Covid-19 Pandemicmentioning
confidence: 99%